Role of the Gut on Glucose Homeostasis: Lesson Learned from Metabolic Surgery - Kamvissi-Lorenz, V. (Curr Atheroscler Rep, 2017)
PURPOSE OF REVIEW: Bariatric surgery was initially intended to reduce weight, and only subsequently was the remission of type two diabetes (T2D) observed as a collateral event. At the moment, the term “metabolic surgery” is used to underline the fact that this type of surgery is performed specifically to treat diabetes and its metabolic complications, such as hyperlipidemia. RECENT FINDINGS: Randomized, controlled studies have recently supported the use of bariatric surgery, and in particular of Roux-en-Y gastric bypass (RYGB) and biliopancreatic diversion (BPD) as an effective treatment for decompensated T2D. The lesson learned from these randomized and many other non-randomized clinical studies is that the stomach and the small intestine play a central role in glucose homeostasis. Bypassing the duodenum and parts of the jejunum exerts a substantial effect on insulin sensitivity and secretion. In fact, with BPD, nutrient transit bypasses duodenum, the entire jejunum and a small portion of the ileum, resulting in reversal of insulin sensitivity back to normal and reduction of insulin secretion, whereas RYGB has little effect on insulin resistance but increases insulin secretion. Hypotheses concerning the mechanism of action of metabolic surgery for diabetes remission vary from theories focusing on jejunal nutrient sensing, to incretin action, to the blunted secretion of putative insulin resistance hormone(s), to changes in the microbiota. SUMMARY: Whatever the mechanism, metabolic surgery has the undoubted merit of exposing the central role of the small intestine in insulin sensitivity and glucose homeostasis.